Report of a Working Group on Allium (Second meeting): Held in Olomouc, Czechoslovakia, 7-9 Jan 1986 - International Board for Plant Genetic Resources; European Cooperative Programme for Plant Genetic Resources; United Nations Development Programme (1986)
Second meeting on a Working Group on Allium